2004
DOI: 10.1113/jphysiol.2003.054932
|View full text |Cite
|
Sign up to set email alerts
|

Actions of noradrenaline on substantia gelatinosa neurones in the rat spinal cord revealed by in vivo patch recording

Abstract: To elucidate the mechanisms of antinociception mediated by the descending noradrenergic pathway in the spinal cord, the effects of noradrenaline (NA) on noxious synaptic responses of substantia gelatinosa (SG) neurones, and postsynaptic actions of NA were investigated in rats using an in vivo whole-cell patch-clamp technique. Under urethane anaesthesia, the rat was fixed in a stereotaxic apparatus after the lumbar spinal cord was exposed. In the currentclamp mode, pinch stimuli applied to the ipsilateral hindl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
120
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 153 publications
(131 citation statements)
references
References 39 publications
9
120
1
1
Order By: Relevance
“…The time necessary for the solution to flow from the stopcock to the surface of the spinal cord was ϳ5 s. The drugs applied were 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX) (Tocris Cookson, St. Louis, MO), DL-2-amino-5-phosphonovaleric acid (APV) (Sigma, St. Louis, MO), strychnine (Sigma), bicuculline (Sigma), methysergide maleate salt (Sigma), ketanserin (Sigma), ondansetron (LKT Laboratories, St. Paul, MN), and RS 23597-190 hydrochloride (Tocris Cookson). The effectiveness of the drugs applied in the same way under in vivo conditions was confirmed in our previous study (Sonohata et al, 2004).…”
Section: Methodssupporting
confidence: 63%
See 3 more Smart Citations
“…The time necessary for the solution to flow from the stopcock to the surface of the spinal cord was ϳ5 s. The drugs applied were 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX) (Tocris Cookson, St. Louis, MO), DL-2-amino-5-phosphonovaleric acid (APV) (Sigma, St. Louis, MO), strychnine (Sigma), bicuculline (Sigma), methysergide maleate salt (Sigma), ketanserin (Sigma), ondansetron (LKT Laboratories, St. Paul, MN), and RS 23597-190 hydrochloride (Tocris Cookson). The effectiveness of the drugs applied in the same way under in vivo conditions was confirmed in our previous study (Sonohata et al, 2004).…”
Section: Methodssupporting
confidence: 63%
“…Because the glutamate antagonists (CNQX and APV) affected neither the amplitude nor frequency of IPSCs during the RVM-ES, we concluded that the RVM-ES-eIPSCs were mediated by monosynaptic GABA A and/or glycinergic receptors. Our previous studies have confirmed that drugs perfused on the surface of the spinal cord act equally on SG neurons, which are located within a range of 30 to 150 m, as do those administered by bath application in slice preparations but not through systemic circulation (Furue et al, 1999;Sonohata et al, 2004).…”
Section: Involvement Of Gaba a And Glycine Receptors In The Rvm-es-eimentioning
confidence: 78%
See 2 more Smart Citations
“…Any delays of first firing to current injections were considered as a delayed firing types of neurons, and other cells were considered as regular firing types. In some cases, the recorded neurons were anatomically identified neurons (29,33) and some populations of interneurons (10), whereas it directly hyperpolarizes the majority of spinal dorsal horn neurons (24,26). A number of experiments have shown the involvement of NA in pelvic organ function and have indicated its multiple actions.…”
mentioning
confidence: 99%